2012
DOI: 10.1016/s0140-6736(11)61453-0
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of coronary artery disease in men: an analysis of the role of the Y chromosome

Abstract: SummaryBackgroundA sexual dimorphism exists in the incidence and prevalence of coronary artery disease—men are more commonly affected than are age-matched women. We explored the role of the Y chromosome in coronary artery disease in the context of this sexual inequity.MethodsWe genotyped 11 markers of the male-specific region of the Y chromosome in 3233 biologically unrelated British men from three cohorts: the British Heart Foundation Family Heart Study (BHF-FHS), West of Scotland Coronary Prevention Study (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
166
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(180 citation statements)
references
References 49 publications
5
166
2
1
Order By: Relevance
“…Haplogroup D2a1 belongs to haplogroup D. It is suggested that as males belonging to haplogroup D2a1 possess significantly higher LH levels than other haplogroups males, haplogroup D males bear a higher prostate cancer risk than other haplogroup males in the Japanese population. Previously, it had been reported that the Y chromosome haplogroup I was associated with 50% of coronary artery disease compared with the other haplogroup, in 1444 British Heart Foundation Family Heart Study and 1534 West of Scotland Coronary Prevention Study (Charchar et al, 2012). However, haplogroup I did not exhibit an association with levels of five sex steroids (testosterone, androstenedione, 5-dehydroepiandrosterone sulfate, estradiol, and estrone) in the 1157 Young Men Cardiovascular Association Study recruited in Silesia, Poland (Bloomer et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Haplogroup D2a1 belongs to haplogroup D. It is suggested that as males belonging to haplogroup D2a1 possess significantly higher LH levels than other haplogroups males, haplogroup D males bear a higher prostate cancer risk than other haplogroup males in the Japanese population. Previously, it had been reported that the Y chromosome haplogroup I was associated with 50% of coronary artery disease compared with the other haplogroup, in 1444 British Heart Foundation Family Heart Study and 1534 West of Scotland Coronary Prevention Study (Charchar et al, 2012). However, haplogroup I did not exhibit an association with levels of five sex steroids (testosterone, androstenedione, 5-dehydroepiandrosterone sulfate, estradiol, and estrone) in the 1157 Young Men Cardiovascular Association Study recruited in Silesia, Poland (Bloomer et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…In addition, there have been reports indicating that there exist associations between Y chromosome haplogroups and male infertility (Kuroki et al, 1999;Krausz et al, 2001;Lu et al, 2007;Yang et al, 2008;Puzuka et al, 2011;Ran et al, 2013;Sato et al, 2013), semen parameters (Sato et al, 2014), and prostate cancer (Ewis et al, 2006;Lindstr€ om et al, 2008;Wang et al, 2012) in some populations, including the Japanese. The Y chromosome haplogroup is also associated with several phenotypes other than male characteristics, including cardiovascular risk (Hiura et al, 2008;Bloomer et al, 2013;Kostrzewa et al, 2013), coronary artery disease (Charchar et al, 2012), lipids (Charchar et al, 2004;Russo et al, 2008), and blood pressure (Charchar et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These conclusions have been reached after genotyping small numbers of known markers, or limited resequencing. Despite the valuable insights that have been obtained, there have been other areas of Y-chromosomal study where uncertainty or debate have persisted for decades, such as the understanding of the causal mutations underlying Y-linked spermatogenic failure (Tyler-Smith and Krausz 2009), the role of Y-chromosomal variation in phenotypes such as coronary artery disease (Charchar et al 2012), or the origins of European male lineages. In the last case, opinions have included a Paleolithic origin for the major lineage (Semino et al 2000), a Neolithic origin for the equivalent lineage (Balaresque et al 2010), and the view that reliable age estimates for this lineage are currently impossible (Busby et al 2011).…”
mentioning
confidence: 99%
“…4 The updated tree provides an important foundation for studies of evolutionary anthropology, 5 genealogical reconstruction, 6 molecular forensics, 7 and medical genetics. 8 Current commercial DNA chips (microarrays) for massive genomewide association studies (GWAS) 9 are designed to contain many Y-SNPs. In 2007, Underhill and Kivisild retrieved 295 Y-SNPs from customized Perlegen arrays in a previous study 10 and used them to reconstruct the Y chromosome tree for 33 males.…”
Section: Introductionmentioning
confidence: 99%